Groundwater potential zone mapping using geographic information systems and multi-influencing factors: A case study of the Kohat District, Khyber Pakhtunkhwa - Faheem, Haris; Khattak, Zeeshan; Islam, Fakhrul; Ali, Rashid; Khan, Rehan; Khan, Ilyas; Tag Eldin, Elsayed (Frontiers in Earth Science, 2023)
Groundwater is a vital component of life; without its identification, it is impossible to live. Therefore, identifying groundwater potential zones (GWPZs) is critical. For this purpose, the study area of the Kohat District was selected to identify GWPZs using the multi-influencing factors (MIF) approach. The Kohat area has a semi-arid to sub-humid subtropical climate and is classified as a sub-tropical, triple-season, semi-arid, sub-mountainous area. The geology, land use, soil, rainfall, lineament density, and drainage density are important parameters of ground water potential identification. The GWPZs were classified into five types: very poor, poor, good, high, and very high. We determined that 37.72% of the study area had high GWPZs, which were predominately in or near the northwest region of the study area, whereas 4.62% of the study area, in the southeast region, had very poor GWPZs. The water table data from the study varied due to different parameters used to identify the GWPZs. Our MIF results revealed that a large area of the Kohat District has good water potential. Still, due to topographic elevation changes, the groundwater potential has been limited in hilly areas. Our final results were compared with water level field data collected from different sources across the Kohat District.